2016
DOI: 10.1111/polp.12184
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Rules and Bureaucratic Effectiveness

Abstract: Literature on comparative institutions shows that electoral and constitutional rules affect the behavior of politicians, while the literature on political control of bureaucracies demonstrates how politicians exercise control over bureaucracies and affect their performance. This article explores how electoral rules affect bureaucratic effectiveness. In particular, I hypothesize that personal vote‐seeking incentives drive legislators to specialize in legislative committees to develop their personal reputations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
6
0
2
Order By: Relevance
“…Source: Authors estimation. Variables [ 1 ] [ 2 ] [ 3 ] [ 4 ] [ 5 ] Static Model Dynamic Model OLS Fixed Effect OLS Fixed Effect Two-step system GMM PHQ PHQ PHQ PHQ PHQ PHQ 0.939*** 0.689*** 0.942*** (0.026) (0.040) (0.046) BQ −0.550*** 0.120 0.003 −0.191 0.059** (0.117) (0.214) (0.049) (0.134) (0.106) CPI −0.624*** −0.210 −0.103*** −0.073 0.121** (0.079) (0.218) (0.035) (0.059) (0.062) Log PoP 0.818*** 0.852*** 0.148*** 0.396*** 0.149*** (0.103) (0.176) (0.045) (0.071) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: Authors estimation. Variables [ 1 ] [ 2 ] [ 3 ] [ 4 ] [ 5 ] Static Model Dynamic Model OLS Fixed Effect OLS Fixed Effect Two-step system GMM PHQ PHQ PHQ PHQ PHQ PHQ 0.939*** 0.689*** 0.942*** (0.026) (0.040) (0.046) BQ −0.550*** 0.120 0.003 −0.191 0.059** (0.117) (0.214) (0.049) (0.134) (0.106) CPI −0.624*** −0.210 −0.103*** −0.073 0.121** (0.079) (0.218) (0.035) (0.059) (0.062) Log PoP 0.818*** 0.852*** 0.148*** 0.396*** 0.149*** (0.103) (0.176) (0.045) (0.071) …”
Section: Resultsmentioning
confidence: 99%
“…Bureaucratic quality (BQ) significantly impacts decision-making and enhances policymakers' capabilities, state capacity, and institutional quality [ [1] , [2] , [3] ]. Many studies have empirically found that expert bureaucratic decision making contributes to adequate national resource allocation and effective utilization of human capital, as well as enhancing the bilateral relations of the state, which in turn promotes institutional quality and the quality of public services [ [4] , [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…Studi lain yang memiliki korelasi secara teoritis dalam temuan penelitian ini adalah (Suryo, 2015) yang membandingkan budaya politik Indonesia dengan negara maju berkesimpulan bahwa sebagai negara yang telah mapan dengan demokrasinya, budaya politik Amerika Serikat bersifat partisipan, sedangkan Indonesia sendiri budaya politiknya relatif konstan dan lebih konsentrasi pada budaya politik parokial dan kaula. Di sisi lain apa yang menjadi temuan Suryo tersebut berbeda dengan temuan (Gehlbach & Simpser, 2014), (Jeong, 2016), (Rogowaki & Porter, 2018) kelompok fungsional guru efektif dalam kemenangan calon atau partai peserta Pemilu. Diantara temuan penelitian sebelumnya adalah (Mahpudin, 2021) dalam studi protest voting dalam Pemilu lokal di Kabupaten Lebak Banten menemukan bahwa kepala daerah memiliki kewenangan yang besar dalam mengelola institusi pendidikan sehingga memiliki peluang untuk memobilisasi para tenaga pendidik untuk kepentingan elektoral.…”
Section: Hasil Dan Pembahasanunclassified
“…The extent to which legislatures are specialized appears to have a positive effect on the efficiency of the bureaucracy. It is found that the degree of legislative specialization has a positive effect on bureaucratic effectiveness in a global sample of 74 countries, and the effect is more pronounced in countries that employ a presidential system (Jeong 2016(Jeong : 1104. Legislatures that have multiple legislative committees tasked with specialized tasks are better suited to 'use ex ante statutory control and ex post oversight of bureaucracies' (Jeong 2016(Jeong : 1095.…”
Section: Legislatures and Effective Governancementioning
confidence: 99%
“…It is found that the degree of legislative specialization has a positive effect on bureaucratic effectiveness in a global sample of 74 countries, and the effect is more pronounced in countries that employ a presidential system (Jeong 2016(Jeong : 1104. Legislatures that have multiple legislative committees tasked with specialized tasks are better suited to 'use ex ante statutory control and ex post oversight of bureaucracies' (Jeong 2016(Jeong : 1095. This is because legislatures with powerful committees are more likely to generate opposition parties that will exercise their oversight responsibilities as concrete policy issues are addressed and debated, compared to legislatures where such committees are amorphouswhich makes it likely that legislatures will not challenge the policies of incumbents (Jeong 2016).…”
Section: Legislatures and Effective Governancementioning
confidence: 99%